Development and Evaluation of A Molecular Diagnostic Method to Rapidly Detect Histoplasma Capsulatum Var. Farciminosum (Causing Epizootic Lymphangitis) from Equine Clinical Samples. (September 2015) - Scantlebury, C.E.; Pinchbeck, G.L.; Loughnane, P.; Ashine, T.; Aklilu, N.; Stringer, A.P.; Gordon, L.; Christley, R.M.; McCarthy, A.J.
Abstract : Reasons for performing study: Histoplasma capsulatum var. farciminosum (HCF), causing epizootic lymphangitis (EZL), is endemic in parts of Africa including, Ethiopia, Senegal and Gambia. Despite its high prevalence, impact on animal welfare and socio‐economic importance, there is little evidence upon which to build practical disease control strategies. The performance and availability of diagnostic tests currently used by clinicians is problematic. Methods such as pattern recognition of clinical signs and microscopy lack specificity and other reported methods are either not commercially available or not readily feasible in these settings (e.g. culture). This is a significant barrier to further understanding this disease within endemic countries. Objectives: To validate a nested PCR method to confirm the presence of HCF in equine clinical samples. Study design: Cross‐sectional. Methods: Twenty‐nine horses with suspected EZL were included from topographically varied regions of Ethiopia. Clinical data, lesion location drawn onto equine silhouettes, blood samples and aspirates of pus from cutaneous nodules were obtained before treatment provided by SPANA clinic. Blood and clinical data were collected from a further 20 horses with no cutaneous EZL lesions. Giemsa stained impression smears of pus were examined microscopically. Aliquots of heat‐inactivated pus and blood were inoculated onto Whatman FTA cards and imported to the UK with Defra approved licensing. A nested PCR targeting the ITS region, was used to identify samples containing HCF and PCR products were sequenced. Results: HCF was confirmed in heat‐inactivated FTA card pus samples from 24 horses, additionally, 23 blood samples were positive from EZL suspected cases. Bioinfomatic analyses suggested that there was diversity within the ITS region among these HCF products. Conclusions: These PCR techniques allow the rapid diagnosis of HCF directly from equine clinical samples. The identification of HCF in blood raises questions about the pathogenesis of HCF in horses and warrants further investigation. Acknowledgements: We thank the SPANA Ethiopia team; participating cart‐horse owners; the Ethio‐Belgian project; Addis Ababa University; Gabrielle Laing and the PHE UK Mycology reference laboratory. Ethical animal research: Ethical approval for the project was awarded from the University of Liverpool and The College of Veterinary Medicine and Agriculture, Addis Ababa University.Sources of funding: SPANA UK (registered charity), the Institute of Infection and Global Health, University of Liverpool and an Sfam studentship.Competing interests: Dr Stringer was veterinary director at SPANA while this project was conducted and provided consultative and logistical input.